TB CO-INFECTION WITH HIV/AIDS: A UNIQUE RADIOLOGICAL PRESENTATION AT LACOR HOSPITAL; A POSTCONFLICT NORTHERN UGANDA. - Kitara, David Lagoro; P., Pirio; D., Acullu; P., Opira C. (African Journal of Infectious Diseases (AJID), 2015)
Background: Tuberculosis (TB) infection is thought to develop at any stage of HIV infection. Pulmonary tuberculosis (PTB) and extra-pulmonary tuberculosis are major complications in HIV/AIDS patients. Tuberculosis is still a diagnostic dilemma in low resource countries, with approximately 68.4% of all active pulmonary cases being negative for AAFBs on sputum. Additionally, it is reported that 46.7% of the active cases have disseminated TB with extra-pulmonary TB; further complicating the diagnosis in post-conflict northern Uganda. We therefore sought to clinically and radiologically characterize the various TB diagnosed in HIV/AIDS patients in this low resource and post conflict environment.Materials and Methods: A prospective cohort study was conducted on 320 sero-positive patients in Lacor Hospital. Clinical features, radiographic and ultrasonographic features of confirmed HIV sero-positive patients with suspected TB co-infection were assessed. Patients were recruited consecutively and the Chest radiographs, thoraco-lumbar and lumbar spine radiographs were taken and analyzed. Trans-thoracic ultrasonography (USS) for justified cases with pleural and pericardial effusion was conducted. FNAB and Tru-cut biopsies were performed for histological confirmation. Cases were followed-up for clinical outcomes (improvement and demise) within 2 months. The ethics and review committee of Gulu University Medical School approved the study and patients who did not meet the inclusion criteria were excluded. Data was analyzed using SPSS 13.0.Results: Atypical Chest x-ray finding included: reticulo-nodular infiltrates (69.7%); hilar and mediastinal adenopathy (40%); pleural effusion (27.5%) and miliary (20.6%). Typical Chest x-ray finding included: Apical reticulo-nodularities and fibro-cavitations (27.5%), and normal Chest x-ray (2.2%). Abdominal Ultrasonographic finding included: porta-hepatis, para-aortic and splenic hilum lymphadenopathy (15.9%); Ascitis (8.1%); TB splenitis (5.3%) and TB nephritis with peri-renal abscess (0.3%). PTB was observed in (53.4%); disseminated TB in (42.2%) and EPTB in (4.4%). Majority (81.9%) of the patients improved and was discharged on DOTS while 18.1% died.Conclusion: Imaging assessment is important adjuvant in HIV/AIDS/TB co-epidemic diagnosis. Early diagnosis and prompt management of TB co-infection ensures longer life and reduce morbidity and mortality.